Effects of Estrous Synchronization of Bali Cattle Using PGF2a - PN, Indira (2014)
The aim of the study was to investigate response, behavior, cycle of estrous and estrogen hormone profile of Bali cattle (Bos sondaicus) which were synchronized by PGF2a. Material samples were 9 Bali cattle at ±3 years old and the average body weight were 313,67±20,66 kg. Bali cattle were synchronized by injection of PGF2a with dosage 5 mg per cattle through intramuscular. Synchronization were covered by two injection with interval 12 days. The bloods were taken before and after injection PGF2a through jugular vein as much as 3 ml per sample. Then bloods samples were analyzed by estrogen hormone kit of Enzyme-Linked Immunosorbent assay (ELISA). The estrous observation was every day. The result showed that response 100% estrus after the post injection PGF2a, onset estrous 57:49±0,55 hours/minutes, estrous indication and behavior were red vulva, mucus, warm, and standing heat, cycle of estrous was 20,11±1,36 days, the concentration of profil estrogen hormones estrus were 35,69±11,83 pg/mL, and non-estrus 25,16±11,92 pg/mL. The study concluded that Bali cattle synchronized using PGF2a showed normal response in onset estrous, behavior and estrous cycle while the concentration estrogen hormones were increased while estrous.